1995
DOI: 10.1093/aje/141.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Does Weight Loss from Middle Age to Old Age Explain the inverse Weight Mortality Relation in Old Age?

Abstract: The authors examined body mass index at middle age, body mass index in old age, and weight change between age 50 years and old age in relation to mortality in old age. The study population from the Established Populations for Epidemiologic Studies of the Elderly consisted of 6,387 whites age 70 years or older who experienced 2,650 deaths during the period 1982-1987. Mortality risk was highest for persons in the heaviest quintile of body mass index at age 50 (men, relative risk (RR) = 1.33, 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
134
4
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(154 citation statements)
references
References 0 publications
14
134
4
2
Order By: Relevance
“…Several previous studies have also demonstrated varying associations between BMI and mortality depending on the analytic approaches used. 5,6,[12][13][14][15][16][17] For example, in the Nurses' Health Study, a J-shaped association was observed in an initial analysis of the entire cohort; however, as seen in our study, a clear linear association emerged in a separate analysis that excluded ever smokers, early deaths and those with significant weight change. 12 In the National Institutes of Health-AARP Diet and Health Study, similar to our finding, BMI at the age of 50 years showed a much stronger positive association with mortality than BMI at study baseline when participants were 50-71 years old.…”
Section: Bmi At Various Ages and Mortality In Chinese Women X Zhang Esupporting
confidence: 39%
“…Several previous studies have also demonstrated varying associations between BMI and mortality depending on the analytic approaches used. 5,6,[12][13][14][15][16][17] For example, in the Nurses' Health Study, a J-shaped association was observed in an initial analysis of the entire cohort; however, as seen in our study, a clear linear association emerged in a separate analysis that excluded ever smokers, early deaths and those with significant weight change. 12 In the National Institutes of Health-AARP Diet and Health Study, similar to our finding, BMI at the age of 50 years showed a much stronger positive association with mortality than BMI at study baseline when participants were 50-71 years old.…”
Section: Bmi At Various Ages and Mortality In Chinese Women X Zhang Esupporting
confidence: 39%
“…This is an issue shared with many other studies 5,26,30 evaluating the BMI mortality relationship. Heyms®eld et al 31 extensively tabulated studies reporting the correlation between self-reported height and weight.…”
Section: Discussionmentioning
confidence: 93%
“…However, after adjusting for weight change from middle-to-old age, BMI in old age was a signi®cant predictor of mortality. This study 30 highlights the value of assessing weight change in addition to utilizing a single weight time-point in understanding mortality outcome.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 The cause of the decrease in BMI among the elderly (Figure 2) is probably mostly chronic fatal disease wasting. 21,22 However, other factors, not associated with poor health, may also play a role. 22 These include sarcopenia, 21 bone-mineral density loss, 23,24 and intentional weight loss.…”
Section: Biases In Mortality Risk Vs Bmi Curvementioning
confidence: 99%
“…21,22 However, other factors, not associated with poor health, may also play a role. 22 These include sarcopenia, 21 bone-mineral density loss, 23,24 and intentional weight loss. 25 One of the important implications of the present study and previously published studies is that a one-point (baseline) determination of BMI is not a reliable mortality predictor in follow-up survival analyses of the mortality risk vs BMI relationship.…”
Section: Biases In Mortality Risk Vs Bmi Curvementioning
confidence: 99%